Bacteriostatic and deodorant insole material and production process thereof
By using the combination of EVA foam base pad and embedded antibacterial deodorization coating in the insole material, the modifier is entangled with chitosan macromolecules to form layered structure silver-carrying ions, which solves the problem of insufficient antibacterial and deodorization performance in the prior art, and achieves efficient antibacterial and deodorization effect and good breathability.
Patent Information
- Application Number
- CN202411985814.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
In practical applications of existing antibacterial insole materials, silver nanoparticles-loaded activated carbon is difficult to release and plays an antibacterial effect, and the deodorization performance is insufficient.
The insole material consisting of EVA foam base pad and antibacterial deodorization coating is adopted. The antibacterial deodorization coating includes components such as aqueous polyurethane resin, aqueous curing agent, embedded antibacterial agent, etc. The embedded antibacterial agent is entangled with chitosan macromolecules through a modifier to form a layered structure, and silver ions are carried to improve antibacterial properties.
It achieves excellent antibacterial and deodorizing properties of insole materials, high breathability, and can effectively reduce the growth of bacteria on the feet and the presence of odor gases, and keep the feet dry.
Smart Images

Figure BDA0005222548650000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to an antibacterial and deodorizing shoe insole material and a production process thereof. Background Art
[0002] As people's awareness of health and comfort continues to improve, especially in the field of daily necessities, the pursuit of a better health experience has become a trend. As the basis of human body contact with the ground, insoles accumulate sweat and secretions for a long time. Especially in summer and after exercise, due to the sharp increase in sweat secretion, microorganisms multiply rapidly, and a large amount of organic matter in sweat is decomposed to produce odor. In the long run, it may even lead to a series of foot diseases such as foot odor, tinea pedis, and athlete's foot, which directly affect people's physical and mental health.
[0003] Existing antibacterial insoles mainly use bactericides or nanomaterials, such as silver salts, chlorhexidine, etc. However, these methods have disadvantages, such as easy loss of bactericides and irritation to the skin, and the safety and environmental impact of nanomaterials are not yet fully clear. Previous studies have combined silver nanoparticles with carbon materials to prepare materials with good antibacterial properties. Using carbon materials as the matrix, the precipitation problem of nanomaterials is effectively solved, while maintaining good and long-lasting antibacterial properties. The most common is silver-loaded activated carbon material; however, in actual applications, silver nanoparticles loaded in activated carbon are difficult to release and exert antibacterial effects, and the antibacterial effect of using only silver-loaded activated carbon is not good. In addition, the activated carbon carrier provides adsorption performance to a certain extent and plays a certain deodorizing role, but it is difficult for the air in the shoe to effectively contact the activated carbon, resulting in insufficient deodorizing performance. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide an antibacterial and deodorizing insole material and a production process thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] An antibacterial and deodorizing insole material, comprising an EVA foam base pad and an antibacterial and deodorizing coating, wherein the antibacterial and deodorizing coating comprises, by weight:
[0007] 100 parts of waterborne polyurethane resin, 5-7 parts of waterborne curing agent, 10-15 parts of embedded antibacterial agent, 1.2-1.8 parts of wetting agent, 1.5-2 parts of defoaming agent, 1-1.5 parts of leveling agent and 2.5-3.5 parts of thickener;
[0008] The embedded antibacterial agent is prepared by the following method:
[0009] Step A1: pre-mix and dilute triethanolamine and dioxane, then add epichlorohydrin and mix well, apply stirring at 60-90 rpm, heat to 45-55°C and react for 1.5-2h, then add triethylamine and mix, introduce compressed nitrogen to increase the pressure and continue to heat to 95-110°C and react for 2-3h, after the reaction is completed, remove dioxane by vacuum rotary evaporation to obtain a modifier;
[0010] Furthermore, the feed ratio of triethanolamine, epichlorohydrin, triethylamine and dioxane is 0.1 mol: 0.3 mol: 10-15 mL: 40-50 mL, and epichlorohydrin reacts with triethanolamine to introduce an epoxy structure for end-capping.
[0011] Step A2: premix the modifier and dimethyl sulfoxide, add chitosan and mix, stir at 30-50 rpm, heat to 60-80°C to swell for 8-12 hours, add silver nitrate solution, stir at 180-240 rpm, slowly add formaldehyde solution to react for 3-4 hours, add water to wash after the reaction, remove the upper aqueous phase by centrifugation, and vacuum dry to obtain a composite precursor;
[0012] Furthermore, the feed ratio of chitosan, modifier, silver nitrate, formaldehyde and dimethyl sulfoxide is 50g:7-11mmol:15-20mmol:80-100mmol:65-80mL, the terminal epoxy structure of the modifier reacts with the active amino group on the chitosan macromolecule to bridge the adjacent chitosan macromolecules to form a chitosan macromolecular entanglement, the nitrogen oxygen structure in the modifier forms a chelating effect, and introduces silver ions into the gaps of the entanglement, which is finally reduced by formaldehyde to form silver doping.
[0013] Preferably, the deacetylation degree of chitosan is not less than 80%, and the chitosan has good swelling property and reactivity.
[0014] Step A3: Place the composite precursor in a muffle furnace, dehydrate and pre-carbonize at 250-300°C for 2.5-3h, then transfer to a vacuum furnace, carbonize and calcine at 820-850°C for 1.5-2h, and after cooling, break up the material to obtain an embedded antibacterial agent.
[0015] A production process of an antibacterial and deodorizing insole material comprises the following steps:
[0016] Step S1: premixing waterborne polyurethane resin, waterborne curing agent, wetting agent, defoaming agent and leveling agent, adding embedded antibacterial agent, stirring and dispersing, adding thickener, mixing and adjusting slurry viscosity, vacuum degassing, and obtaining functional coating;
[0017] Step S2: Scrape the functional coating onto the surface of the EVA foam base pad, and then pre-bake it into a film and hot-press it to obtain an antibacterial and deodorizing insole material.
[0018] Preferably, the pre-baking film-forming temperature is 60-70° C., the time is 40-60 min, and the hot pressing composite temperature is 120-140° C., the time is 120-160 s.
[0019] Preferably, the functional coating has a viscosity of 1200-1500 mPa·s, and it is easy to be scraped and formed within this viscosity range.
[0020] Preferably, the scraping amount of the functional coating is 420-550g / m 2 Under the control of the coating amount, the coating has good mechanical properties and maintains better comfort and breathability.
[0021] Beneficial effects of the present invention:
[0022] The invention discloses an insole material with a composite structure. The conventional EVA foam material is used as a substrate to maintain good comfort of the insole. The composite antibacterial and deodorizing coating is used to give the insole excellent antibacterial and deodorizing performance. The manufacturing process is simple and is conducive to realizing mass production. The antibacterial and deodorizing coating is based on polyurethane and is compounded with an embedded antibacterial agent independently developed. The antibacterial and deodorizing coating is formed by reacting epichlorohydrin with triethanolamine to form a modifier with branched epoxy end-capping. The end epoxy structure of the modifier reacts with the active amino group on the swollen chitosan macromolecule to bridge adjacent chitosan macromolecules to form chitosan macromolecular entanglements. The nitrogen-oxygen structure in the modifier forms a chelating effect to introduce silver ions into the gaps of the entanglements. After being reduced by formaldehyde, the antibacterial and deodorizing coating is formed. It is doped with silver and finally formed by roasting and carbonization. Compared with the existing silver-loaded activated carbon, the entanglement of the modifier and the chitosan macromolecule forms a large number of layered structures after carbonization, and the reduced silver forms a supporting role in the layered gaps, so that the embedded antibacterial agent presents a large number of layered pores, which are compounded in the coating to form a breathable channel, so that the coating has excellent air permeability, which is conducive to the permeation of water such as sweat stains on the feet, and can keep the feet dry. The silver element loaded in the pores is impregnated with water to release silver ions, which has excellent antibacterial properties and reduces the growth of bacteria on the feet. In addition, these layered pores have a large internal surface area and have activated carbon as the pore wall, which has a strong adsorption capacity for odorous gases. When the odorous gases in the shoes flow through these pores, the odor can be adsorbed to achieve a deodorizing effect. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] During this implementation process, the information of raw materials is disclosed as follows:
[0025] Chitosan, industrial-grade chitosan raw material from Jiangsu Kangting Biotechnology Co., Ltd., with a deacetylation degree of 82%; water-based polyurethane resin, PU-657 raw material from Shanghai Bolino New Material Technology Co., Ltd.; water-based curing agent, CL-9169 raw material from Shanghai Bolino New Material Technology Co., Ltd.; wetting agent, AG-183 raw material from Guangdong Zhongtai Lianhua New Material Co., Ltd.; defoaming agent, ZB-220 raw material from Jinan Zhongbei Fine Chemical Co., Ltd.; leveling agent, JF-804H raw material from Jiashan Jiangnan Textile Materials Co., Ltd.; thickener, H416C raw material from Hefei Huayue New Material Technology Co., Ltd.;
[0026] Example 1, preparation of antibacterial and deodorizing insole materials, specifically as follows:
[0027] (1) Preparation of embedded antimicrobial agent
[0028] Step A1: pre-mix and dilute triethanolamine and 1,0-dioxane, then add epichlorohydrin and mix well, stir at 90 rpm, heat to 55°C and react for 1.5 h, then add triethylamine and mix, introduce compressed nitrogen to increase the pressure to 8 bar, continue to heat to 110°C and react for 2 h, wherein the feed ratio of triethanolamine, epichlorohydrin, triethylamine and 1,0-dioxane is 0.1 mol: 0.3 mol: 10 mL: 50 mL, and after the reaction, remove 1,0-dioxane by vacuum rotary evaporation to obtain a modifier.
[0029] Step A2: pre-mix the modifier and dimethyl sulfoxide, add chitosan and mix, apply stirring at 50 rpm, heat to 80°C for swelling for 8 hours, add silver nitrate solution, apply stirring at 240 rpm, slowly add formaldehyde solution to react for 3 hours, wherein the feed ratio of chitosan, modifier, silver nitrate, formaldehyde and dimethyl sulfoxide is 50g:11mmol:20mmol:100mmol:80mL, the silver nitrate solution is a saturated solution at room temperature, the mass fraction of the formaldehyde solution is 10%, add water to wash after the reaction is completed, centrifuge to remove the upper aqueous phase, and vacuum dry to obtain a composite precursor.
[0030] Step A3: Place the composite precursor in a muffle furnace, dehydrate and pre-carbonize at 300°C for 2.5 hours, then transfer to a vacuum furnace, carbonize and calcine at 850°C for 1.5 hours, and then disassemble and disassemble after cooling to obtain an embedded antibacterial agent.
[0031] (2) Preparation of antibacterial and deodorizing insole materials
[0032] Step S1: premix the waterborne polyurethane resin, waterborne curing agent, wetting agent, defoaming agent and leveling agent at 60 rpm for 10 min, add the embedded antibacterial agent prepared in this embodiment, stir and disperse at 600 rpm for 3 min, then add the thickener and mix to adjust the slurry viscosity, vacuum degassing, and obtain the functional coating;
[0033] Step S2: Take the EVA foam base pad and apply the functional coating on the surface, controlling the coating amount to 550g / m 2 , sent into a tunnel oven, baked at 60°C for 60 minutes for pre-baking into a film, and then transferred to a hot press machine for hot pressing at 140°C for 160 seconds for hot pressing and compounding to obtain the antibacterial and deodorizing insole material.
[0034] Example 2, preparation of antibacterial and deodorizing insole materials, as follows:
[0035] (1) Preparation of embedded antimicrobial agent
[0036] Step A1: pre-mix and dilute triethanolamine and 1,000 mmol / l, then add epichlorohydrin and mix well, stir at 60 rpm, heat to 45°C and react for 2 h, then add triethylamine and mix, introduce compressed nitrogen to increase the pressure to 5 bar, continue to heat to 95°C and react for 3 h, wherein the feed ratio of triethanolamine, epichlorohydrin, triethylamine and 1,000 mmol / l is 0.1 mol: 0.3 mol: 15 mL: 40 mL, and after the reaction, remove 1,000 mmol / l by vacuum rotary evaporation to obtain a modifier.
[0037] Step A2: pre-mix the modifier and dimethyl sulfoxide, add chitosan and mix, stir at 30 rpm, heat to 60°C for swelling for 12 h, add silver nitrate solution, stir at 180 rpm, slowly add formaldehyde solution and react for 4 h, wherein the feed ratio of chitosan, modifier, silver nitrate, formaldehyde and dimethyl sulfoxide is 50 g: 7 mmol: 15 mmol: 80 mmol: 65 mL, the silver nitrate solution is a saturated solution at room temperature, the mass fraction of the formaldehyde solution is 10%, after the reaction is completed, add water to wash, centrifuge to remove the upper aqueous phase, and vacuum dry to obtain a composite precursor.
[0038] Step A3: Place the composite precursor in a muffle furnace, dehydrate and pre-carbonize at 250°C for 3 hours, then transfer to a vacuum furnace, carbonize and calcine at 820°C for 2 hours, and then disassemble and disassemble after cooling to obtain an embedded antibacterial agent.
[0039] (2) Preparation of antibacterial and deodorizing insole materials
[0040] Step S1: premix the waterborne polyurethane resin, waterborne curing agent, wetting agent, defoaming agent and leveling agent at 60 rpm for 15 min, add the embedded antibacterial agent prepared in this embodiment, stir and disperse at 600 rpm for 5 min, then add the thickener and mix to adjust the slurry viscosity, vacuum degassing, and obtain the functional coating;
[0041] Step S2: Take the EVA foam base pad and apply the functional coating on the surface, controlling the coating amount to 420g / m 2, sent into a tunnel oven, baked at 70°C for 40 minutes for pre-baking into a film, and then transferred to a hot press machine for hot pressing at 120°C for 120 seconds to obtain an antibacterial and deodorizing insole material.
[0042] Example 3, preparation of antibacterial and deodorizing insole materials, as follows:
[0043] (1) Preparation of embedded antimicrobial agent
[0044] Step A1: pre-mix and dilute triethanolamine and epichlorohydrin, then add epichlorohydrin and mix well, stir at 90 rpm, heat to 50°C and react for 1.8 hours, then add triethylamine and mix, introduce compressed nitrogen to increase the pressure to 6 bar, continue to heat to 100°C and react for 2.5 hours, wherein the feed ratio of triethanolamine, epichlorohydrin, triethylamine and dioxane is 0.1 mol: 0.3 mol: 12 mL: 45 mL, and after the reaction, remove dioxane by vacuum rotary evaporation to obtain a modifier.
[0045] Step A2: pre-mix the modifier and dimethyl sulfoxide, add chitosan and mix, apply stirring at 30 rpm, heat to 70°C for swelling for 10 hours, add silver nitrate solution, apply stirring at 240 rpm, slowly add formaldehyde solution to react for 3.5 hours, wherein the feed ratio of chitosan, modifier, silver nitrate, formaldehyde and dimethyl sulfoxide is 50g:9mmol:17mmol:90mmol:70mL, the silver nitrate solution is a saturated solution at room temperature, the mass fraction of the formaldehyde solution is 10%, add water to wash after the reaction is completed, centrifuge to remove the upper aqueous phase, and vacuum dry to obtain a composite precursor.
[0046] Step A3: Place the composite precursor in a muffle furnace, dehydrate and pre-carbonize at 270°C for 2.6 hours, then transfer to a vacuum furnace, carbonize and calcine at 830°C for 1.7 hours, and then disassemble and disassemble after cooling to obtain an embedded antibacterial agent.
[0047] (2) Preparation of antibacterial and deodorizing insole materials
[0048] Step S1: premix the waterborne polyurethane resin, waterborne curing agent, wetting agent, defoaming agent and leveling agent at 60 rpm for 12 min, add the embedded antibacterial agent prepared in this embodiment, stir and disperse at 600 rpm for 4 min, then add the thickener and mix to adjust the slurry viscosity, vacuum degassing, and obtain the functional coating;
[0049] Step S2: Take the EVA foam base pad and apply the functional coating on the surface, controlling the coating amount to 480g / m 2 , sent into a tunnel oven, baked at 60°C for 50 minutes for pre-baking into a film, and then transferred to a hot press machine for hot pressing at 130°C for 150 seconds for hot pressing and compounding to obtain the antibacterial and deodorizing insole material.
[0050] Example 4, preparation of antibacterial and deodorizing insole materials, as follows:
[0051] (1) Preparation of embedded antimicrobial agent
[0052] Step A1: pre-mix and dilute triethanolamine and epichlorohydrin, then add epichlorohydrin and mix well, stir at 90 rpm, heat to 50°C and react for 2 h, then add triethylamine and mix, introduce compressed nitrogen to increase the pressure to 7 bar, continue to heat to 100°C and react for 2.2 h, wherein the feed ratio of triethanolamine, epichlorohydrin, triethylamine and dioxane is 0.1 mol: 0.3 mol: 12 mL: 40 mL, and after the reaction, remove dioxane by vacuum rotary evaporation to obtain a modifier.
[0053] Step A2: pre-mix the modifier and dimethyl sulfoxide, add chitosan and mix, stir at 50 rpm, heat to 70°C for swelling for 12 hours, add silver nitrate solution, stir at 180 rpm, slowly add formaldehyde solution and react for 3.5 hours, wherein the feed ratio of chitosan, modifier, silver nitrate, formaldehyde and dimethyl sulfoxide is 50g:10mmol:18mmol:90mmol:75mL, the silver nitrate solution is a saturated solution at room temperature, the mass fraction of the formaldehyde solution is 10%, after the reaction is completed, add water to wash, centrifuge to remove the upper aqueous phase, and vacuum dry to obtain a composite precursor.
[0054] Step A3: Place the composite precursor in a muffle furnace, dehydrate and pre-carbonize at 300°C for 2.5 hours, then transfer to a vacuum furnace, carbonize and calcine at 830°C for 1.8 hours, and then disassemble and disassemble after cooling to obtain an embedded antibacterial agent.
[0055] (2) Preparation of antibacterial and deodorizing insole materials
[0056] Step S1: premix the waterborne polyurethane resin, waterborne curing agent, wetting agent, defoaming agent and leveling agent at 60 rpm for 15 min, add the embedded antibacterial agent prepared in this embodiment, stir and disperse at 600 rpm for 5 min, then add the thickener and mix to adjust the slurry viscosity, vacuum degassing, and obtain the functional coating;
[0057] Step S2: Take the EVA foam base pad and apply the functional coating on the surface, controlling the coating amount to 500g / m 2 , sent into a tunnel oven, baked at 65°C for 60 minutes for pre-baking into a film, and then transferred to a hot press machine for hot pressing at 120°C for 150 seconds for hot pressing and compounding to obtain the antibacterial and deodorizing insole material.
[0058] In the above implementation process, the dosage ratio and viscosity test of the functional coating are shown in Table 1:
[0059] Table 1
[0060] Example 1 Example 2 Example 3 Example 4 Waterborne polyurethane resin 100 100 100 100 Water-based curing agent 7 5 6 6 Embedded antimicrobial agent 10 15 13 12 Wetting Agents 1.2 1.8 1.5 1.5 Defoaming agent 1.5 2 1.8 1.7 Leveling agent 1 1.5 1.3 1.2 Thickener 3 3.5 2.5 2.8 Viscosity / mPa·s 1410 1480 1225 1320
[0061] Comparative example, referring to Example 4, the intercalated antibacterial agent is replaced with the same weight portion of ZLIP-AG type silver-loaded activated carbon (grinding fineness is 325 mesh), and 0.3 parts of LD904 type silver antibacterial agent are added, and the rest of the implementation process is exactly the same.
[0062] In order to facilitate the detection of the relevant properties of the antibacterial and deodorizing coating, the functional coating prepared in the above process was scraped on the surface of the glass fiber board, cured and formed according to the relevant process parameters, the antibacterial and deodorizing coating was peeled off, and the samples were taken for tensile test according to GB / T 10654-2001, tear test according to GB / T 10808-2006, and air permeability test according to GB / T 10655-2003. The specific test results are shown in Table 2:
[0063] Table 2
[0064] Tensile strength / MPa <![CDATA[Tear strength / N·mm -1 > <![CDATA[Air permeability / mm·s -1 > Example 1 1.22 8.87 19.1 Example 2 1.05 7.59 25.2 Example 3 1.34 9.84 22.4 Example 4 1.29 10.06 23.9 Comparative Example 1.17 9.31 9.6
[0065] It can be seen from the test results in Table 2 that the coatings of the embodiment and the comparative example have good mechanical properties and are well compatible with the EVA foam base pad. The air permeability of the coating of the embodiment is much higher than that of the comparative example, which is beneficial to the water discharge from the foot.
[0066] Samples were taken from the coating stripped as above, and the antibacterial test was carried out according to GB / T 21866-2008 standard, with Escherichia coli and Staphylococcus aureus as the test bacteria, and the culture period was 48 hours; samples were taken from the coating stripped as above, and sealed and clamped with a rubber clamp, with syringes connected at both ends, and odorous gas (hydrogen sulfide and ammonia were used in the experiment, respectively) was introduced into the syringe at one end, and the odorous gas content was m 0 , push the odorous gas through the coating sample into another syringe with a thrust of 1kgf, and detect the odorous gas content again, recorded as m 1 , deodorization rate = (m 0 -m 1 ) / m 0 ×100%, the specific test results are shown in Table 3:
[0067] Table 3
[0068]
[0069] It can be seen from the test results in Table 3 that both the examples and the comparative examples have good antibacterial effects, and the examples are extremely excellent in deodorization.
[0070] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0071] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. An antibacterial and deodorizing insole material, comprising an EVA foam base pad and an antibacterial and deodorizing coating, characterized in that: The antibacterial and deodorizing coating comprises, by weight: 100 parts of waterborne polyurethane resin, 5-7 parts of waterborne curing agent, 10-15 parts of embedded antibacterial agent, 1.2-1.8 parts of wetting agent, 1.5-2 parts of defoaming agent, 1-1.5 parts of leveling agent and 2.5-3.5 parts of thickener; The embedded antibacterial agent is prepared by the following method: Step A1: pre-mix and dilute triethanolamine and dioxane, then add epichlorohydrin and mix well, stir and heat to 45-55°C for reaction for 1.5-2h, then add triethylamine and mix, introduce compressed nitrogen to increase the pressure and continue to heat to 95-110°C for reaction for 2-3h, after the reaction is completed, remove dioxane by vacuum rotary evaporation to obtain a modifier; Step A2: premix the modifier and dimethyl sulfoxide, add chitosan, stir and heat to 60-80°C to swell for 8-12 hours, add silver nitrate solution, stir and slowly add formaldehyde solution to react for 3-4 hours, add water to wash after the reaction, centrifuge to remove the upper aqueous phase, and vacuum dry to obtain a composite precursor; Step A3: Place the composite precursor in a muffle furnace, dehydrate and pre-carbonize at 250-300°C for 2.5-3h, then transfer to a vacuum furnace, carbonize and calcine at 820-850°C for 1.5-2h, and after cooling, break up the material to obtain an embedded antibacterial agent.
2. The antibacterial and deodorizing insole material according to claim 1, characterized in that: The feed ratio of triethanolamine, epichlorohydrin, triethylamine and dioxane is 0.1 mol: 0.3 mol: 10-15 mL: 40-50 mL.
3. The antibacterial and deodorizing insole material according to claim 2, characterized in that: The feed ratio of chitosan, modifier, silver nitrate, formaldehyde and dimethyl sulfoxide is 50g:7-11mmol:15-20mmol:80-100mmol:65-80mL.
4. The antibacterial and deodorizing insole material according to claim 3, characterized in that: The deacetylation degree of chitosan is not less than 80%.
5. The production process of an antibacterial and deodorizing insole material according to claim 4, characterized in that: Including the following processes: Step S1: premixing waterborne polyurethane resin, waterborne curing agent, wetting agent, defoaming agent and leveling agent, adding embedded antibacterial agent, stirring and dispersing, adding thickener, mixing and adjusting slurry viscosity, vacuum degassing, and obtaining functional coating; Step S2: Scrape the functional coating onto the surface of the EVA foam base pad, and then pre-bake it into a film and hot-press it to obtain an antibacterial and deodorizing insole material.
6. The production process of an antibacterial and deodorizing insole material according to claim 5, characterized in that: The viscosity of the functional coating is 1200-1500mPa·s.
7. The production process of an antibacterial and deodorizing insole material according to claim 6, characterized in that: Functional coating scraping weight 420-550g / m 2 .
8. The production process of an antibacterial and deodorizing insole material according to claim 7, characterized in that: The pre-baking film forming temperature is 60-70°C, the time is 40-60min, and the hot pressing composite temperature is 120-140°C, the time is 120-160s.